Pengawasan Pengelolaan Tanah Wakaf Dalam Kewenangan KUA Kecamatan Nanggung Kabupaten Bogor dalam Pendekatan Konsep Kesejahteraan Sosial - Ani Yumarni; Ani Nuraeni; Hidayat Rumatiga (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
Endowment management has special principles, namely the principles of sustainability and eternity. This principle of eternity can be manifested in the form of optimizing the performance of nazhir (endowment organiser) and the District Office of Religious Affairs (KUA) which functions as manager, supervisor and recorder of the orderly administration of endowment in Indonesia. Due to the wide and large distribution of endowment land throughout Indonesia, the government, in this case the Indonesian Ministry of Religion, appointed the role and function of KUA elements as executors and supervisors of endowment. The style and allocation of waqf in each sub-district is different. This article analyzes the role and authority of the KUA of Nanggung District, Bogor Regency in carrying out its functions. In particular, the allocation of endowment in Nanggung District is still limited to '3M' endowment, namely masjid-musala, madrasa, and burial ground. This research uses a empirical juridical approach which is descriptive analytical and explanatory. This research provides an overview and analysis of endowment organiser and supervision practices by nazhir and by the KUA institution by linking this implementation to applicable laws and regulations. The results of this research show that the role and function of the Nanggung District KUA has been implemented optimally. The role of guidance and supervision runs optimally as seen in the endowment land which is registered and monitored from the aspect of ownership, handover of the endowment to the aspect of the performance of the nazhir as the endowment organiser.